Penerapan E-CRM Dalam Strategi Pemasaran Online Barang Retail Rumah Tangga - Manurung, Silpany; Sembiring, Muhammad Ardiansyah; Azmi, Sri Rezki Maulina (Institut Teknologi Garut, 2025)
This study explores the implementation of Electronic Customer Relationship Management (E-CRM) as a strategic approach to enhance the effectiveness of online marketing in the household goods retail business, Adele Grosir Kisaran, located in Asahan Regency, North Sumatra. The primary challenges identified include the absence of digital promotional tools, the lack of a computerized transaction system, and limited customer communication. To address these issues, an integrated web-based E-CRM system was developed using the PHP CodeIgniter framework and MariaDB database. Key features include customer registration, product catalog, digital ordering and payment, feedback system, real-time chat, and automated notifications for promotions and loyalty programs. A qualitative approach was employed, involving observation, interviews, and literature review, while system evaluation was conducted through black-box testing to ensure functional compliance. Customer data analysis revealed that the E-CRM implementation not only improved transaction efficiency and service communication but also generated behavioral patterns that could be explored through association rules. For instance, an association rule with 35% support and 78% confidence indicated that customers who purchased kitchenware also tended to buy household cleaning supplies. This pattern formed the basis for targeted promotional strategies, which proved to increase customer response rates by 25% compared to previous promotional methods. This research contributes to the digital transformation literature of MSMEs by demonstrating how the integration of E-CRM and customer data analysis can strengthen data-driven decision-making. The study offers a replicable system model for other MSMEs to enhance competitiveness, reinforce customer relationships, and achieve business sustainability in a highly competitive digital era.